Das ruas ao ciberespaço: ativismo e ciberativismo de mulheres negras - Silva, Mona Lisa da (2019)
From the 1988 constitution and the redemocratization process of the country in the mid1980s-1990s, Brazil was in a socio-historical-political and economic period that allowed the emergence of many Non-governmental organization (NGOs) and social movements - including the Black women political movement. Cyberspace, from the second half of the nineties onwards, provided NGOs and Social Movements with a space where counterhegemonic narratives from these groups would gain strength, reach other people and other contexts through technical-communicational processes that facilitated interaction and political mobilization of these movements. That said, this dissertation seeks to understand, from the Network of Black Cyberactivists-CE, how the cyberactivism of black women contributes and / or can contribute to the black feminism, specifically, as well as to the political mobilizations of the black movement, in general. In order to reach the goal established in this study, we opted for the research methodology of qualitative nature and anthropological basis, which uses the ethnography in online environments, also known as netnography, of Robert V, Kozinets (2014). To reach the proposed objectives, a discussion was initially presented on the basis of black American feminist thinking from black women considered to be black pioneers. Then, the trajectory of the Brazilian black women's movement was traced through movements from the pre-abolition to cyberspace. Finally, the movement of black women in cyberspace was presented through the Black Cyberactivists Network.